Devotional Spaces and Noble Women’s Religiosity in Early Modern Spain Aranda and Híjar Lineages - Malo Barranco, Laura (Cuadernos de Historia Moderna, 2017)
In Early Modern Spain, noble women developed their faith in different religious spaces. Privately, since they were little girls, they learned from the religious pieces of art that adorned their houses’ rooms and listened the holy mass next to their ladies-in-waiting in little oratories and chapels placed inside noble family homes. At the same time, noble women were part too of the religious practices shared with the complete society of this period. Some of them were educated in convents that saw them later taking vows and choosing religion as their way of life; another ones, destined to marriage, lived their devotion together with the common of the people in parishes and brotherhoods. Their faith was linked to their lineage’s cults and proprieties, whose wealth gave women the possibility of becoming religious patrons and live their faith in a privileged way.
Keywords: Woman; Nobility; Devotion; Oratory; Religious Practices; Feminine Patronage